A linguagem de crianças com Síndrome Congênita do Zika Vírus um guia para profissionais - Verdu, Ana Cláudia Moreira Almeida (Editora Oficina Universitária, 2021)
This guide presents information for professionals in the field of health and education, which aims to explain how communication develops in children with Congenital Zika Virus Syndrome. It is also intended for professionals who are involved in the process of language acquisition and development for these children. It presents guidelines that can contextually meet the real needs of children diagnosed with Congenital Zika Virus Syndrome. It is understood that this guide will not solve all the doubts of the professionals who assist this population, but it presents important information about the communication problems of the children and the main doubts of the family.